2021
DOI: 10.1055/a-1339-0913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simple, specific, verbal instructions on the quality of bowel preparation in hospitalized patients undergoing colonoscopy: a multicenter randomized controlled trial

Abstract: Background and study aims Bowel preparation for colonoscopy is frequently inadequate in hospitalized patients. We explored the impact of specific verbal instructions on the quality of inpatients bowel preparation and factors associated with preparation failure. Patients and methods Randomized (1:1), two strata (mobilized vs. bedridden; 3:2) trial of consecutive inpatients from four tertiary centers, who received either specific, verbal instructions or the standard of care (SOC) ward instructions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
(48 reference statements)
0
9
0
1
Order By: Relevance
“…First, it was conducted at a single center and was a single-arm, retrospective study, which may cause bias of the results. Second, it has demonstrated that patient-related factors like drugs intake, previous abdominal surgery, and chronic constipation may be associated with an increased risk of inadequate preparation; nevertheless, we did not enroll these factors, which may influence the accuracy of the results (26)(27)(28)(29). Third, past research showed that poor patient compliance may also cause inadequate bowel preparation (30).…”
Section: Discussionmentioning
confidence: 99%
“…First, it was conducted at a single center and was a single-arm, retrospective study, which may cause bias of the results. Second, it has demonstrated that patient-related factors like drugs intake, previous abdominal surgery, and chronic constipation may be associated with an increased risk of inadequate preparation; nevertheless, we did not enroll these factors, which may influence the accuracy of the results (26)(27)(28)(29). Third, past research showed that poor patient compliance may also cause inadequate bowel preparation (30).…”
Section: Discussionmentioning
confidence: 99%
“…For 2 of them (models A and C [6,8]), the cutoff value that most accurately predicts the inadequate bowel preparation is provided, while for the third one (model B [7]) an online calculator predicting the probability of inadequate bowel preparation for each patient is available. For the purposes of this study, the raw data of a previous prospective randomized (1:1), 2 strata (mobilized vs. bedridden; 3:2) trial of consecutive inpatients from 4 tertiary centers in Greece, evaluating the role of simple and specific verbal instructions in improving the bowel preparation of inpatients (mobilized and bedridden, defined as in previous iterations [9,10]) undergoing colonoscopy were assessed to calculate the respective values for each score/model [10]. The protocol of the study was approved by the Attikon University General Hospital Ethics Committee (EBΔ 1677/6-7-16) and is available in the ClinicalTrials.gov registry (NCT02887014).…”
Section: Methodsmentioning
confidence: 99%
“…Patients enrolled in the original validation cohort received bowel cleansing with 4 L of polyethylene glycol solution along with a 2-day low-fiber diet, followed by a clear liquid diet the day before the colonoscopy. Bowel preparation was administered either as split doses or as same day (day before) dosing, according to the time of the colonoscopy (morning or afternoon examinations), while all examinations were performed 4-6 h after the intake of cathartics was completed [10]. Each model's comportments and cutoff values, as well as the main characteristics of their derivation/ validation cohort and their efficacy in predicting the quality of bowel preparation are depicted in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben der Wahl des Abführmittels und der Frage welcher Zeitpunkt der Einnahme günstig ist, ist die Art der Aufklärung zur Darmvorbereitung wichtig [26]. In einer kürzlich veröffentlichten Studie erhielten die Patienten 4 Liter einer PEG-Lösung, gemeinsam mit einer zweitägigen ballaststoffarmen Kost und einer flüssigen Kost am Tag vor der Koloskopie.…”
Section: Konzepte Zur Darmvorbereitung Vor Koloskopieunclassified